New insights into the provision of health services in Indonesia : a health workforce study - Rokx, Claudia, 1964- (Directions in development (Washington, D.C.). Human development., 2010)
Indonesia has made improving the access to health workers, especially in rural areas, and improving the quality of health providers key priority areas of its next five-year development plan. Significant steps and policy changes were taken in the past to improve the distribution of the health force, but few studies have been undertaken to measure the actual impact of these policies and programs. This study begins the process of reviewing the impacts of the past policies and policy changes. It links the changes in supply and quality of health workers to past health work force policies but also t.